2013
DOI: 10.5507/bp.2012.099
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between BRCA1 expression and clinicopathological factors including brain metastases in patients with non-small-cell lung cancer

Abstract: Background. Previously identified as a breast and ovarian cancer susceptibility gene, BRCA1 has gained major scientific interest as a potential prognostic and/or predictive marker for various tumors, including non-small-cell lung cancer (NSCLC), the leading cause of cancer related mortality worldwide. BRCA1 plays a central role in DNA damage response (DDR. It undergoes phosphorylation by various DDR kinases at different serine residues, of which ser1524 is known to be specifically phosphorylated by ATM in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…The results of the current meta-analysis which summarized 11 studies involving 1041 patients showed that positive BRCA1 expression was associated with a shorter OS and DFS without regional disparities. The conclusion was consistent with the results of the previous studies[ 18 , 21 , 25 , 26 ]. BRCA1 expression status could serve as a novel indicator for the assessment of prognosis and formulation of therapy strategy for resected NSCLC patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the current meta-analysis which summarized 11 studies involving 1041 patients showed that positive BRCA1 expression was associated with a shorter OS and DFS without regional disparities. The conclusion was consistent with the results of the previous studies[ 18 , 21 , 25 , 26 ]. BRCA1 expression status could serve as a novel indicator for the assessment of prognosis and formulation of therapy strategy for resected NSCLC patients.…”
Section: Discussionsupporting
confidence: 93%
“…The sample sizes ranged from 32 to 221 and the proportion of patients with BRCA1 expression ranged from 13.1% to 66.7%. Furthermore, Gachechiladze et al [ 21 ] performed subgroup analysis based on the TNM stage and provided sufficient data of the two groups, so we considered them as two studies during the process of statistical analyses. Other specific information is summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The role of ATM in BRCA1 phosphorylation and the interaction of these proteins is established 166,167 . In addition, variants of ATM and BRCA1 have functional effects in breast cancer 141,168 .…”
Section: Breast To Brain Metastasesmentioning
confidence: 99%
“…Gachechiladze et al 166 reported a significant correlation between shorter survival and phosphorylation of BRCA1 in patients with brain metastases of lung cancer. The role of ATM in BRCA1 phosphorylation and the interaction of these proteins is established 166 , 167 . In addition, variants of ATM and BRCA1 have functional effects in breast cancer 141 , 168 .…”
Section: Breast To Brain Metastasesmentioning
confidence: 99%
“…Σε άλλη μελέτη έχει αναφερθεί ότι τόσο το BRCA1 όσο και το KRAS αποτελούν για την Ένα φαινόμενο, το οποίο δεν πρέπει να παραλείψουμε να αναφέρουμε (λόγω της μεγάλης συσχέτισής του με το γονίδιο BRCA) είναι η σχέση με την αναιμία Fanconi. Έχει διατυπωθεί από καιρό ότι η αναιμία Fanconi και η σηματοδοτική οδός του BRCA συσχετιζόμενες αφού μεταλλάξεις στο BRCA προκαλούν την παραπάνω αναιμία[103,[151][152][153]. Ταυτοχρόνως, έχει δειχθεί ότι όχι μόνο η παρουσία μεταλλάξεων στο γονίδιο Μια από τις σημαντικότερες ομάδες είναι οι DNA damage response BRCT περιοχές, οι οποίες πήραν το όνομά τους από τις περιοχές στο καρβόξυ-τελικό άκρο της πρωτεΐνης BRCA1[160][161][162][163][164][165][166][167][168][169].…”
unclassified